Obstetric and Neonatal Outcome of Pregnancies Fathered by Males on Immunosuppression After Solid Organ Transplantation. Issue 6 (13th April 2015) - Morken, N.‐H.; Diaz‐Garcia, C.; Reisaeter, A. V.; Foss, A.; Leivestad, T.; Geiran, O.; Hervás, D.; Brännström, M.
<x xml:space="preserve">Abstract</x> Immunosuppressive drugs may influence spermatogenesis, but little is known about outcome of pregnancies fathered by transplanted males. We estimated risk of adverse outcomes in pregnancies (with data after the first trimester) fathered by males that had undergone organ transplantation and were treated with immunosuppression. A population‐based study, linking data from the Norwegian transplant registry and the Medical Birth Registry of Norway during 1967–2009 was designed. All Norwegian men undergoing solid organ transplantation were included. Odds ratios for major malformations, preeclampsia, preterm delivery (<37 weeks) and small‐for‐gestational‐age were obtained using logistic regression. A total of 2463 transplanted males, fathering babies of 4614 deliveries before and 474 deliveries after transplantation were identified. The risk of preeclampsia was increased (AOR: 7.4, 95% CI: 1.1–51.4, ) after transplantation compared to prior to transplantation. No increased risk was found for congenital malformations or other outcomes when compared with pregnancies before transplantation or with the general population (2 511 506 births). Our results indicate an increased risk of preeclampsia mediated through the transplanted and immunosuppressed father. Importantly, no increased risk was found for other adverse obstetric outcomes or malformations, which may reassure male transplant recipients planning to father children.